2007
DOI: 10.1016/j.acn.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and neuroimaging correlates of pediatric traumatic brain injury: A diffusion tensor imaging (DTI) study

Abstract: This study examined the sensitivity of diffusion tensor imaging (DTI) to microstructural white matter (WM) damage in mild and moderate pediatric traumatic brain injury (TBI). Fourteen children with TBI and 14 controls ages 10-18 had DTI scans and neurocognitive evaluations at 6-12 months post-injury. Groups did not differ in intelligence, but children with TBI showed slower processing speed, working memory and executive deficits, and greater behavioral dysregulation. The TBI group had lower fractional anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(180 citation statements)
references
References 70 publications
6
169
2
2
Order By: Relevance
“…[162][163][164][165][166] These discrepancies may be due, in part, to the considerable spatial heterogeneity in the brain areas examined, 167 as well as differences in the postinjury interval. FA may still have prognostic value, with evidence suggesting that the direction and magnitude of change correlates with clinical outcomes; 166,168 however, this idea awaits validation in both paediatric and adult populations. FA might lack the necessary sensitivity to fully appreciate changes in white matter tract integrity following brain injury, and measures of diffusivity may be more appropriate.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%
“…[162][163][164][165][166] These discrepancies may be due, in part, to the considerable spatial heterogeneity in the brain areas examined, 167 as well as differences in the postinjury interval. FA may still have prognostic value, with evidence suggesting that the direction and magnitude of change correlates with clinical outcomes; 166,168 however, this idea awaits validation in both paediatric and adult populations. FA might lack the necessary sensitivity to fully appreciate changes in white matter tract integrity following brain injury, and measures of diffusivity may be more appropriate.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%
“…Significant differences in the FA, ADC, or MD, or other DTIderived diffusivity metrics have been demonstrated in studies of TBI in both adults (Bigler et al, 2010b;Kraus et al, 2007;Lipton et al, 2008;Perlbarg et al, 2009;Warner et al, 2010a) and children (Ewing-Cobbs et al, 2008;Levin et al, 2008;McCauley et al, 2011;Wilde et al, 2006bWilde et al, , 2010Wozniak et al, 2007;Wu et al, 2010a;Yuan et al, 2007), with decreases in FA and increases in measures of diffusivity often found in chronic post-injury intervals. More importantly, changes in DTIderived measures have shown correlation with injury severity (Arfanakis et al, 2002;Benson et al, 2007;Wilde et al, 2010;Yuan et al, 2007), functional outcome (Huisman et al, 2004;Levin et al, 2008;Salmond et al, 2006;Wozniak et al, 2007), neurologic functioning (Caeyenberghs et al, 2010a,b), and cognitive ability (Bigler et al, 2010b;Ewing-Cobbs et al, 2008;Kraus et al, 2007;Kumar et al, 2009;Levin et al, 2008;McCauley et al, 2011;Niogi et al, 2008;Salmond et al, 2006;Warner et al, 2010a;Wilde et al, 2010). Longitudinal studies have also indicated that DTI might serve as a tool for revealing changes in the neural tissue during recovery from TBI (Bendlin et al, 2008;Sidaros et al, 2008;Wu et al, 2010a).…”
Section: Fig 1 Ct (A)mentioning
confidence: 99%
“…An additional consideration in assessing the child or adolescent athlete with a concussion is that in the clinical evaluation by the healthcare professional there may be the need to include both patient and parent input as well as teacher and school input when appropriate. (101)(102)(103)(104)(105)(106)(107) The decision to use NP testing is broadly the same as the adult assessment paradigm. However, timing of testing may differ in order to assist planning in school and home management (and may be performed while the patient is still symptomatic).…”
Section: The Child and Adolescent Athletementioning
confidence: 99%